Agent Moose - O'Hara, Mo (a Feiwel and Friends, an imprint of MacMillan Publishing Group, 2020)
"Something fishy is going on at the South Shore. Folks just disappear and are never seen again. But when Agent Moose learns that a key witness has gone missing, he and Owlfred ride to the rescue. Will they find the missing turtle before time runs out?"--Amazon.